Features of money origin and its evolution - Govorushko, Tamara; Sytnyk, Inna; Rozvaga, Lesia (My University, 2014)
The article deals with the questions of money origin and proper understanding of its role in the life of any modern society. Its historical evolution from the simplest goods to ways of expressing the value was investigated. The existence of commodity production, scientific and economic research into the money origin have formed different views. It's necessary to explore these issues in detail and show the local and international vision of the problem because modern economy is exposed to constant changes and transformation.
Keywords: finance; conception; money; functions; form; фінанси; гроші; концепція; финансы; концепция; деньги; кафедра фінансів